Lictorella carolina Fraser 1911 - Calder, Dale R.; Choong, Henry H. C. (Zenodo, 2018)
Lictorella carolina Fraser, 1911 Lictorella carolina Fraser, 1911: 53, pl. 4, figs. 3–5. Zygophylax carolina .— Rees & Vervoort, 1987: 71. Zygophylax carolinus Cairns et al ., 1991: 24. Holotype. See Remarks below. Type locality. USA, Washington: San Juan Archipelago (Fraser 1911). Current status. Valid, as Zygophylax carolina (Fraser, 1911). Remarks. Fraser (1911) described Lictorella carolina from a single detached specimen that may not have constituted a complete colony. Rees & Vervoort (1987) considered an “imperfectly preserved specimen labelled: ‘ Lictorella carolina Fraser. San Juan. T. Kincaid’" in the NMNH to be type material and probably the holotype of the species (No. 70625, with No. 34084 on a separate label). The collection could not be located in the online database of the NMNH under either number during this study. Neither could the specimen be found during a visit by one of us (DRC) to the NMNH in September 2017. Hydroids of L. carolina in the Fraser Hydroid Collection at the RBCM (BCPM 976-00334-001: Trinity Islands, 20 August 1914, 91 m, dry; BCPM 976-00335-001: Gulf of Alaska) (Arai 1977) are not types. Additional information on morphology of this species, beyond the original description, exists in Fraser (1914b). Rees & Vervoort (1987) remarked that the hydroid, as Zygophylax carolina , was “insufficiently described” and founded on sterile material. Nevertheless, Z. carolina has been listed as valid in Cairns et al . (2002, as Z. carolinus ), Antsulevich (2015), and WoRMS. Published as part of Calder, Dale R. & Choong, Henry H. C., 2018, Names of hydroids (Cnidaria, Hydrozoa) established by Charles McLean Fraser (1872 - 1946), excluding those from Allan Hancock Expeditions, pp. 1-83 in Zootaxa 4487 (1) on page 37, DOI:10.11646/zootaxa.4487.1.1, http://zenodo.org/record/1456161